2021
DOI: 10.1021/acsami.1c10067
|View full text |Cite
|
Sign up to set email alerts
|

Lizard-Skin-Inspired Nanofibrous Capillary Network Combined with a Slippery Surface for Efficient Fog Collection

Abstract: Freshwater shortage is a critical global issue that needs to be resolved urgently. Efficient water collection from fog provides a promising and sustainable solution to produce clean drinking water, especially in the desert and arid regions. Nature has long served as our best source of inspiration for designing new structures and developing new materials. Herein, we report a strategy to design a novel Janus fog collector with a hydrophilic lizard-skin-like nanofibrous network upper surface and hydrophobic slipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Zhang et al reported a bottom-up strategy involving the implementation of an innovative coating and electrospinning method to design a Janus fog collector with a hydrophilic nanofiber network upper surface and a hydrophobic smooth lower surface. 19 Hu et al prepared an integrated system to enhance water collection efficiency by applying a top-down strategy in which a micro− nanostructured tapered spine is combined with a Janus membrane through an integrative electrochemical corrosion and hydrothermal method. 20 In addition, because of the unique mechanism of interaction between a femtosecond laser and materials, the femtosecond laser has been widely used in micro−nanostructure direct writing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported a bottom-up strategy involving the implementation of an innovative coating and electrospinning method to design a Janus fog collector with a hydrophilic nanofiber network upper surface and a hydrophobic smooth lower surface. 19 Hu et al prepared an integrated system to enhance water collection efficiency by applying a top-down strategy in which a micro− nanostructured tapered spine is combined with a Janus membrane through an integrative electrochemical corrosion and hydrothermal method. 20 In addition, because of the unique mechanism of interaction between a femtosecond laser and materials, the femtosecond laser has been widely used in micro−nanostructure direct writing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, various methods such as chemical synthesis, oxidation, deposition, electrospinning, hydrothermal methods, and laser direct writing have been used to prepare Janus structures. Zhang et al reported a bottom-up strategy involving the implementation of an innovative coating and electrospinning method to design a Janus fog collector with a hydrophilic nanofiber network upper surface and a hydrophobic smooth lower surface . Hu et al prepared an integrated system to enhance water collection efficiency by applying a top-down strategy in which a micro–nanostructured tapered spine is combined with a Janus membrane through an integrative electrochemical corrosion and hydrothermal method .…”
Section: Introductionmentioning
confidence: 99%
“…The wrinkled PDMS bilayer system we prepared exhibited water collection efficiency, which is almost thrice as that of similar systems reported in the literature (Table S2, Supporting Information). [ 54,55 ] Also, our system shows directionality in water collection property and reusability. Water collection from fog occurs in four steps: i) vapor condensation, ii) water droplet growth, iii) coalescence, and iv) sliding.…”
Section: Resultsmentioning
confidence: 94%
“…Electrospinning is a simple and versatile technology for fabricating fibrous cellular network structures at micro- and nanoscales. During electrospinning, the highly charged nanofibers deposited on the substrate self-assemble into a cellular network structure under the competitive action of surface tension and electrostatic repulsion. Based on available literature, we believe such a unique structure integrating hydrophilic bumps and a hydrophobic slippery surface designed from electrospun nanofibers may not only promote fog capture, droplet growth, and coalescence but also will facilitate directional transport of coalesced moisture/water. ,, …”
Section: Introductionmentioning
confidence: 99%